Towards Universal Health Coverage in Brazil - Fava, Virgínia Maria Dalfior (2021)
Publisher Copyright: © 2021, International Society of Global Health. All rights reserved. Funding The authors certify that they have no affiliation with or involvement in any organization or entity with any financial interest (such as honoraria, educational grants, participation in speakers’ bureaus, membership, employment, consultancies, stock ownership, or other equity interest, and expert testimony or patent-licensing arrangements), or non-financial interest (such as personal or professional relationships, affiliations, knowledge or beliefs) in the subject matter or materials discussed in this manuscript. The authors also certify that this work was not supported by any public or private funding agency.